Understanding Prisoner Victimisation - Daems, Tom; Goossens, Elien (Palgrave Studies in Victims and Victimology, 2024)
1 The safety paradox and beyond: why we should study inter-prisoner victimisation -- 2 Who’s who? Individual characteristics of those involved in sexual assaults in adult men’s prisons in England and Wales -- 3 Every victim is unique: Explaining victimisation among prisoners in Flanders -- 4 The victim-offender overlap in prisons -- 5 Vulnerability and victimhood in prison -- 6 Independent monitoring and victimisation in prisons -- 7 Methodological challenges to victimisation studies.